PL.83 Trends in Caesarean Section in the East of Scotland. (26th April 2013) - Laxman, V; Balakumar, V; Nicoll, A
Abstract : Aims: In Tayside in 2012 we observed an increase in the rate of caesarean section (CS). Our aim was to determine the cause of this and to develop strategies that might prevent further increase. Methods: A prospective longitudinal audit was performed. All women who required CS in July 2012 were included. Robson's classification (RC) was used to categorise women. Women who had CS in July 2007 were identified using the local maternity database (Torex Protos Evolution) and these were also categorised for comparison. Results: In 2007 77/353 (21.8%) and in 2012 86/377 (22.8%) required CS (p = N/S). For both groups the most frequent category was RC5 (multiparous, ≥37 weeks, previous CS). In 2007 27/77 (35%) were RC5 and in 2012 35/86 (40%) were RC5. In 2007 the next category was RC10 (≤36 weeks) (12/77, 15.5%). However in 2012 this accounted for 3/86 (3%) (p = 0.03). In 2012 the second largest group was RC2 (primiparous induced/CS prior to labour). This had increased from 7/77 (9%) in 2007 to 19/86 (22%) in 2012 (p = 0.03). For both groups the next category was RC6 (primiparous breech). In 2007 1/77 (1%) were RC6 and in 2012 6/86 (7%) were RC6 (p = N/S) Conclusions: In Tayside the main indication for CS is previous CS. Promoting vaginal birth after caesarean (VBAC) might halt the rise in CS. We have introduced an information leaflet that promotes VBAC. There are a significant number of primiparous women having CS prior to the onset of labour or following induction of labour. Effective counselling and decision making will ensure that these women are managed appropriately. Reference: Robson's classification of Caesarean Section.